FORMATION OF METAL IN GROSVENOR MOUNTAINS 95551 AND COMPARISON TO ORDINARY CHONDRITES - Campbell A.J.; Humayun M. (My University, 2003)
Siderophile element abundances in individual metal grains in the ungrouped chondrite Grosvenor Mountains (GRO) 95551 and in the ordinary chondrites Tieschitz H3.6, Soko-Banja LL4, and Allegan H5 were measured with laser ablation-inductively coupled plasma mass spectrometry. Matrix metal in GRO 95551 falls into two distinct compositional groups, a high-Ni group with 7.2 +/- 0.4 wt% Ni and a low-Ni group with 3.7 +/- 0.1 wt% Ni, indicating that kamacite/taenite equilibration at ~1020 K was followed by rapid cooling. The nonrefractory siderophile elements P, Co, Cu, Ga, Ge, As, Pd, and Au also partition between the high-Ni and low-Ni metal in a manner consistent with kamacite/taenite fractionation, but the refractory siderophiles Ru, Re, Os, Ir, and Pt show correlated variations that are unrelated to kamacite/taenite partitioning and indicate that variations in refractory components of the metal were not completely erased during equilibration at ~1020 K. The Ni-normalized bulk metal composition of GRO 95551 is refractory depleted and volatile rich relative to Bencubbin and related metal-rich chondrites but bears strong similarities to equilibrated ordinary chondrite metal. GRO 95551 represents a new chondrite type with chemical affinity to the ordinary chondrites. Individual metal grains in unequlibrated ordinary chondrites also have correlated variations in refractory siderophile contents that cannot be produced by redox processes alone; these variations span three orders of magnitude and diminish with increasing metamorphic grade of the ordinary chondrites.